The Impact of Application of the Humanistic Nursing Model on Quality of Life and Satisfaction with Nursing among Breast Cancer Patients - Qiujuan Mao; Hui Zhang; Jing Huang; Juan Liu; Liping Yang (Tehran University of Medical Sciences, 2022)
No Abstract